Pengaruh Work Stress dan Employee Engagement Terhadap Turnover Intention dengan Employee Well-Being Sebagai Variabel Mediasi - Destiana Putri, Femayla; Khandias Akbar, Yunata; Rojuaniah, Rojuaniah; Puspitaloka Mahadewi, Erlina (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
High employee turnover remains a major challenge for financing companies as it can increase recruitment costs, disrupt organizational operations, and result in the loss of competent employees. Several factors may contribute to this issue, including work stress, employee engagement, and employee well-being. Therefore, this study aims to examine the effects of work stress and employee engagement on turnover intention, with employee well-being serving as a mediating variable. This study employed a quantitative approach using a survey method involving employees of financing companies in Jakarta. A total of 170 respondents participated in the study, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that work stress positively affects turnover intention and negatively affects employee well-being. Employee engagement positively affects employee well-being but has no effect on turnover intention. Furthermore, employee well-being negatively affects turnover intention and mediates the relationships between work stress and turnover intention as well as between employee engagement and turnover intention. These findings highlight the important role of employee well-being in reducing turnover intention. Therefore, employee well-being should be prioritized as part of human resource management strategies to reduce turnover intention and improve employee retention.